The impact of expressive writing of deep feelings about labor experiences on postpartum depression: a randomized clinical controlled trial - Sara Mohammadi; Fatemeh Hadizadeh Talasaz; Fatemeh Mohammadzadeh; Jahanshir Tavakolizadeh; Narjes Bahri (BMC Psychology)
Abstract Objective This study aimed to evaluate the expression of deep feelings about labor experiences in a virtual group of peers on the rate of postpartum depression. Methods This randomized clinical trial was conducted on 154 women who had given birth at a public hospital in Birjand city, in the North East of Iran, between May and October 2019. The participants were randomly allocated into two groups using four permuted blocks (the emotion expression and the control group). The participants fulfilled the Edinburgh Postnatal Depression Scale and a demographic questionnaire 6–72 h after delivery. For two weeks and twice a day, the intervention group wrote about the deepest thoughts and feelings about their experiences during labor and delivery in their peers’ virtual social media group. The control group shared information about their daily life events or daily baby care experiences in another virtual social media group of their peers. The Edinburgh Postnatal Depression Scale was completed again by the participants at the end of the second week and three months after delivery. Data were analyzed using the Generalized Estimation Equations model. P < 0.05 was set as the level of statistical significance. Results The participants had a mean age of 27.7 years (SD = 5.2), with no significant differences observed between the two groups in terms of demographic and reproductive characteristics (p-values > 0.05). The results of the Generalized Estimation Equation model indicated that there was no statistically significant difference in depression scores between the two groups 6–72 h after childbirth (p = 0.404). Additionally, the analysis showed that the changes in depression scores over time did not significantly differ between the control and intervention groups following the intervention. This suggests that both groups experienced similar patterns of change in their depression scores (p = 0.112). Conclusion Overall, the results showed that the expression of deep feelings about labor experiences in a virtual social media group of peers does not affect the rate of postpartum depression. More clinical trials with larger sample sizes are needed to draw better conclusions. Registry of clinical trial Iranian Registry of Clinical Trial (IRCT). Registration number: IRCT20190610043859N1. Date of registration: 12/08/2019.